On the determination of the quasiparticle scattering rate in unconventional superconductors by microwave surface impedance - Cherpak, N.T.; Barannik, A.A.; Prozorov, R.; Tanatar, M.; Velichko, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
As found from numerous microwave experiments on the unconventional Fe-based superconductors, the temperature dependence of the quasiparticle scattering rate t–1 cannot be accurately described within the framework of standard Drude module in the popular approximation of wt << 1, where w is the signal frequency. To account for the discrepancy, we have extended the classical Drude model for the case of arbitrary values of wt, and obtained the expression for t–1 as a function of experimentally measurable quantities, namely the real and imaginary parts of the microwave surface impedance. We then show the temperature dependence of t–1 in supercon-ducting Ba(Fe1–xCox)2As2 single crystal pnictide derived from the Ka-band surface impedance measurements within the framework of the modified expression. The measurements indicate the extent to which assumption of wt << 1 gives results different from those obtained without this restriction, i.e., incorrect results.